Monitoring Pengaruh Suhu Pada Panel Surya Terhadap Performa Keluaran Pembangkit Listrik Tenaga Surya - Indra Bayu, Jaya; Budi Sulistiyawati, Irrine; Putu Agustini, Ni (Jurnal FORTECH, 2023)
The sun is an alternative energy source that is currently being utilized, by using solar panels to capture light and process it into the electrical power we need. The performance of solar panels is strongly influenced by several parameters including panel surface temperature, ambient temperature, and solar irradiance. This research makes a solar irradiation sensor using solar panels as a substitute for a pyranometer and adds temperature and wind speed sensors to determine the effect on PLTS performance. To find out the temperature, the PV surface temperature uses the DS18B20 sensor and the ambient temperature sensor uses the DHT11 sensor. Anemometer sensors use wind speed to find out, then each sensor is configured with an Arduino microcontroller so that it can operate and display the required data. The test results obtained the effect of wind speed on the performance of solar panels.